2013
DOI: 10.2105/ajph.2012.300876
|View full text |Cite
|
Sign up to set email alerts
|

Giving to Others and the Association Between Stress and Mortality

Abstract: Helping others predicted reduced mortality specifically by buffering the association between stress and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
96
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 43 publications
8
96
0
2
Order By: Relevance
“…Compassion appears to buffer the effects of stress on wellbeing (Poulin, Brown, Dillard, & Smith, 2013). Also, the other-oriented focus of the compassionate response may allow the observer to empathize with the other's suffering but without identifying with it, providing a self-other distinction which is essential to regulate personal distress feelings and to provide adequate care to the sufferer (Klimecki and Singer, 2012).…”
Section: Compassionmentioning
confidence: 99%
“…Compassion appears to buffer the effects of stress on wellbeing (Poulin, Brown, Dillard, & Smith, 2013). Also, the other-oriented focus of the compassionate response may allow the observer to empathize with the other's suffering but without identifying with it, providing a self-other distinction which is essential to regulate personal distress feelings and to provide adequate care to the sufferer (Klimecki and Singer, 2012).…”
Section: Compassionmentioning
confidence: 99%
“…Perhaps most importantly, compassion appears to buffer the effects of stress on well-being. A study conducted on over 800 people found that while stress generally predicted greater mortality, this link was absent in those who were engaged in compassionate activities [32], perhaps because it improves resilience and increases adaptive profiles of stress reactivity [33]. As a consequence, individuals who engage in compassionate actions show improved health and longer lifespans [34,35].…”
Section: The Benefits Of Compassion For Patients and Providersmentioning
confidence: 99%
“…Given the extent of burnout and stress in the medical field [11,59], the desire on the part of providers, medical staff, and patients for more compassionate interactions [20,24,29] and the stress-buffering and health-promoting impact of compassion [32,35], it is imperative that healthcare providers avail themselves of tools to help decrease burnout and increase compassion. While efforts are being made to reduce stress in medical schools [60], the millions of providers already in practice are in need of tools that are beneficial and time-effective.…”
Section: Implications For Decreasing Burnoutmentioning
confidence: 99%
“…Providing indirect support for this hypothesis, correlational and longitudinal research suggests that individuals who provide help to others exhibit a reduced risk of mortality and better overall health (e.g., Brown, Consedine & Magai, 2005;Brown et al, 2009;Piliavin & Siegl, 2007;Poulin, Brown, Dillard & Smith, 2013; see Konrath & Brown, 2013 for a recent review).…”
mentioning
confidence: 99%